2014
DOI: 10.1080/09712119.2013.875915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary threonine:lysine ratios on growth performance, blood urea nitrogen, and nitrogen balance in weaned pigs

Abstract: Two experiments were conducted to evaluate the effects of different levels of threonine:lysine (Thr:Lys) ratios on growth performance, blood urea nitrogen (BUN) concentration, and nitrogen balance in weaned pigs. In Experiment 1, a total of 90 weaned pigs (Landrace × Yorkshire × Duroc) with an initial average body weight (BW) of 6.57 ± 0.46 kg were allocated into three treatments for 35 days. Each treatment had six replicate pens with five pigs per pen. Diets were formulated with different apparent ileal diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…In Exp. 2, piglets raised under unclean sanitary conditions had reduced growth performance compared with the values reported by other studies (335 g, NRC, 2012 ; 500 g, Zhang and Kim, 2014 ). This suggests that the sanitation model of immune challenge was effective, which is consistent with the findings of others ( Lee et al., 2005 , Le Floc’h et al., 2006 , Kahindi et al., 2014a ) that showed decreased growth performance when piglets subjected to poor sanitary conditions.…”
Section: Discussionmentioning
confidence: 51%
“…In Exp. 2, piglets raised under unclean sanitary conditions had reduced growth performance compared with the values reported by other studies (335 g, NRC, 2012 ; 500 g, Zhang and Kim, 2014 ). This suggests that the sanitation model of immune challenge was effective, which is consistent with the findings of others ( Lee et al., 2005 , Le Floc’h et al., 2006 , Kahindi et al., 2014a ) that showed decreased growth performance when piglets subjected to poor sanitary conditions.…”
Section: Discussionmentioning
confidence: 51%
“…Com base nestes valores, pode-se inferir que as temperaturas médias de máxima e mínima ficaram acima da zona de conforto térmico, indicado por Campos et al (2009) Não foi observado efeito (P<0,05)) das relações treonina e lisina sobre o consumo de ração dos animais nos períodos I e II. Os achados no presente trabalho é semelhante aos resultados encontrados por Zhang et al (2014) ao avaliarem níveis crescentes de treonina para leitões em crescimento (6 a 32 kg), e também por Wang et al (2006Wang et al ( , 2007 que não constataram variação significativa no consumo médio de ração dos leitões, quando avaliaram níveis de treonina e lisina digestíveis da ração para suínos jovens. Tais trabalhos demonstram que os leitões são capazes de tolerar consideráveis excessos de aminoácidos sem que ocorra diferença significativa no consumo voluntário de ração por esses animais.…”
Section: Resultsunclassified
“…Em relação ao ganho de peso dos leitões não foi verificada diferença (P>0,05) entre os tratamentos em ambos os períodos. Zhang et al (2014), ao avaliarem níveis crescentes de treonina para leitões desmamados aos 21 dias, também não observaram influência dos níveis deste aminoácido sobre o ganho de peso, o que indica que a redução dos seus níveis foi tal que não comprometeu a deposição de proteína desses animais. Resultados similares também foram encontrados por Pozza et al 2000e Paiano et al (2009) que trabalharam com diferentes níveis de treonina para leitões em fase de crescimento.…”
Section: Resultsunclassified
“…It was consistent with Figueroa et al (2012) who stated that supplementation with lysine increased growth performance and the lysine requirement might be higher than the level suggested by NRC (1998) for fattening pigs or for the pigs that had a greater potential for lean tissue deposition. However, Zhang and Kim (2014) reported that the dietary lysine concentration was sufficient for the growth of weaned pigs according to NRC (1998).…”
Section: Growth Performancesmentioning
confidence: 99%